Analyzing The Implementation Of The Merdeka Curriculum In Islamic Religious Education: A Case Study At Surya Buana Islamic Elementary School - Shobihatul Fitroh Noviyanti; Melanie Rohmalia; Laysa Azka Umais Syalwa; Muhammad Riyan Firnanda (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The implementation of the Merdeka Curriculum in Islamic Religious Education at Surya Buana Islamic Elementary School represents a significant shift from traditional lesson plans to structured teaching modules that emphasize flexibility and student-centered learning. This study aims to analyze how the school integrates the Merdeka Curriculum into Islamic Religious Education and how teachers adapt teaching modules to enhance learning quality and respond to diverse student needs. A qualitative approach was employed, using observation, interviews, and document analysis to obtain comprehensive data on curriculum implementation and classroom practices. The findings indicate that Surya Buana Islamic Elementary School has successfully implemented the Merdeka Curriculum by developing teaching modules that are flexible, contextual, and aligned with students’ developmental characteristics. Teachers apply interactive and differentiated learning strategies, which support students’ engagement, character development, and understanding of religious values. The transition from lesson plans to teaching modules has also improved instructional planning, allowing teachers to design more meaningful and adaptive learning experiences. The practical significance of this study lies in providing an empirical example of how the Merdeka Curriculum can be effectively implemented in Islamic Religious Education at the elementary level. The findings offer practical guidance for teachers and school leaders in designing teaching modules and implementing differentiated learning, and they may serve as a reference for other schools seeking to adopt and adapt the Merdeka Curriculum in religious education contexts.